2020
DOI: 10.1002/chem.201905160
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Attachment of a Gold(I) Phosphine Moiety at the Upper Rim of a Calix[4]pyrrole on the Binding of Tetraalkylammonium Chloride Salts

Abstract: We report the synthesis of an unprecedented mono‐gold(I) phosphine complex based on a “two‐wall” aryl‐ethynyl extended calix[4]pyrrole. We describe and compare the binding properties of the parent 10α,20α‐bis‐aryl‐ethynyl calix[4]pyrrole ligand and the prepared organometallic compound as receptors for tetraalkylammonium chloride salts in dichloromethane and acetone. We describe the results of 1H NMR, UV–Vis titrations and isothermal titration calorimetry (ITC) experiments in dichloromethane and acetone, aiming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…31 P{ 1 H} NMR spectra show in all cases only one signal that is 10 -20 ppm downfield shifted with respect to the AuClPPh3 or (AuCl)2(diphosphane) precursors, as an indication of the successful formation of pure products. [29][30][31] Figure 1. 1 H NMR spectrum of compound 1a in CDCl3.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…31 P{ 1 H} NMR spectra show in all cases only one signal that is 10 -20 ppm downfield shifted with respect to the AuClPPh3 or (AuCl)2(diphosphane) precursors, as an indication of the successful formation of pure products. [29][30][31] Figure 1. 1 H NMR spectrum of compound 1a in CDCl3.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…1 H NMR (δ(TMS) = 0.0 ppm) and 31 The crystal data and experimental details for the data collection of 1a, 2b and 3 are given in Table S1-3. The single crystal data for all compounds were collected using a Bruker-Nonius KappaCCD diffractometer with an APEX-II detector with graphitemonochromatized Mo-Kα (λ = 0.71073 Å) radiation.…”
Section: Physical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using in vitro studies with different cancer cell lines, the authors demonstrated that the cytotoxic activity of the compounds derived from the co-existence of the calix [4]pyrrole element and the bound Pt(II) metal center. Recently, we described the synthesis and characterization of the anion receptor 1Au based on a mono-nuclear gold(I) acetylide complex containing a "two wall" calix [4]pyrrole as recognition element for anions [12]. We installed the acetylide gold(I) complex as para-substituent of one of the meso-aryl groups of the "two wall" aryl extended calix [4]pyrrole 1Au.…”
Section: Introductionmentioning
confidence: 99%
“…We also describe the results of the 1 H NMR titration experiments of receptor 2Au and its synthetic precursors, 2 and 3, with TBACl in dichloromethane and acetone solution. We perform ITC experiments and pair-wise competitive experiments for the accurate thermodynamic characterization of [4]pyrrole 1; (b) equilibrium between the two putative conformers of the 1:1 complexes of the mono-nuclear calix [4]pyrrole receptor 1Au with chloride, Cl − ⊂1Au, hypothesized in our previous work [12].…”
Section: Introductionmentioning
confidence: 99%